Barriers to the Development of Creative Industries in Culturally Diverse Region - Andrzej Klimczuk (Coactivity: Philosophy, Communication, 2014)
The aim of this article is to describe the general conditions for the development of creative industries in Podlaskie Voivodship from Poland. This region on the background of the country is characterized by the highest level of cultural diversity and multiculturalism policy. However, there are a number of barriers for the creative industries. First article discusses the regional characteristics and then the basic theoretical approaches and conclusions of the author's own research. The following sections discuss the conclusions and recommendations for regional policy and management of cultural sector entities that may be relevant also for other culturally diverse regions.
Keywords: R58; Z10; L38; A14; 330; regional policy; diversity; management of cultural institutions; creative industries; Regional policy; Diversity management; Cultural economics; Creative industries